Drug release from triple-layered microparticles of various sizes - Low, Zheng Yang. (2011)
Drug delivery application involving the subcutaneous or intramuscular administration requires particle size to be 5 um to 150 um. It has been shown in multiple studies that particle size is one of the primary determinants of drug release rate. The aim of this study was to investigate the effect of the particle size of triple-layered (poly (lactide-co-glycolide)/poly (L-lactide)/poly (ethylene-co-vinyl acetate)) microparticles on the release rate of an encapsulated drug upon exposure to release medium. The study will be done with the following size range, 150 – 106 um, 106 – 75 um, 75 – 53 um, 53 – 38 um and 38 – 10 um. Ibuprofen loaded triple-layered microparticles were prepared with an oil-in-water solvent extraction technique and sieved to achieve these size ranges. In vitro drug release conducted in phosphate buffer of pH 7.4 were measured. Subsequently, differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and size exclusion chromatography (SEC) were used to monitor the morphological changes and degradation behaviour of the microparticles upon exposure to the release medium. Based on these experimental results, it is possible to conclude the following phenomena: smaller microparticles have a faster drug release rate, degradation effect of middle layer poly (L-lactide) as a rate-limiting barrier diminishes with reduced size due to overcompensation of diffusion mechanism, and small triple-layered microparticles display a more consistent release with reduced burst effect compared to single-layered and DL microparticles.